Клинико-функциональная оценка эффективности кинезиотейпирования при восстановительном лечении цервикогенной головной боли у детей = Clinical and functional assessment of the effectiveness kinesiotaping reductive treatment of cervicogenic headache in children - Gorsha, O. V.; Korolenko, N. V. (Journal of Education, Health and Sport, 2016)
Gorsha O. V., Korolenko N. V. Клинико-функциональная оценка эффективности кинезиотейпирования при восстановительном лечении цервикогенной головной боли у детей = Clinical and functional assessment of the effectiveness kinesiotaping reductive treatment of cervicogenic headache in children. Journal of Education, Health and Sport. 2016;6(1):333-340. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45474 http://ojs.ukw.edu.pl/index.php/johs/article/view/3370 https://pbn.nauka.gov.pl/works/711643 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.01.2016. Revised 12.01.2016. Accepted: 31.01.2016. Клинико-функциональная оценка эффективности кинезиотейпирования при восстановительном лечении цервикогенной головной боли у детей Clinical and functional assessment of the effectiveness kinesiotaping reductive treatment of cervicogenic headache in children О. В. Горша, Н. В. Короленко O. V. Gorsha, N. V. Korolenko Клинический отдел медицинской реабилитации ГП УКРНИИ МТ МОЗ Украины, г.Одесса Одесский областной благотворительный фонд реабилитации детей-инвалидов «Будущее», г. Одесса Ukrainian Scientific and Research Institute of Transport Medicine, Odessa Odessa Regional Charitable Foundation Rehabilitation of Disabled Children "The Future", Odessa Abstract In the dynamic follow-up (before and after rehabilitation treatment) there were 53 children under school age with cervicogenic headaches against the background of instability in the cervical spine and blood vessels disorders dyscirculatory vertebrobasilar basin. The study showed that the use on the neck kinezioteypov reduces pathological influence on hemodynamic instability, which provides a reduction or cessation of headaches, feeling better. The effectiveness of the secondary kinezioteypirovaniya cervicogenic headaches against the background of instability in the cervical spine the urgency of further research. Keywards: children, cervicogenic headache, hemodynamics, recovery treatment, kinesiotaping. Реферат В динамическом наблюдении (до и после восстановительного лечения) находилось 53 ребёнка младшего школьного возраста с цервикогенной головной болью на фоне нестабильности в шейном отделе позвоночника и дисциркуляторными нарушениями кровотока сосудов вертебробазилярного бассейна. Исследование показало, что применение на область шеи кинезиотейпов позволяет уменьшить патологическое влияния нестабильности на гемодинамику, что обеспечивает уменьшение или прекращение головной боли, улучшение самочувствия. Эффективность применения кинезиотейпирования при вторичной цервикогенной головной боли на фоне нестабильности в шейном отделе позвоночника обосновывает актуальность дальнейших исследований. Ключевые слова: дети, цервикогенная головная боль, гемодинамика, восстановительное лечение, кинезиотейпирование.